PENGARUH KESADARAN MEREK, PERSEPSI KUALITAS, CITRA MEREK, DAN LOYALITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN SIMCARD DATA IM3 (STUDI PADA SMA N 1 SUKOREJO) - Anton Purnomo, 12.05.51.0108; Maskur, Ali (Students' Journal of Economic and Management, 2016)
With so many communications company in Indonesia, then consumers will be more selective in determining im card that will be used as their needs. The problem in this research is "whether the variable of brand awareness, perceived quality, brand image and brand loyalty influence on purchase decisions in SMA 1 Sukorejo. The number of samples in this study of 100 respondents, the sampling technique used was accidental sampling in which respondents are all employees da students in SMA 1 Sukorejo. Collecting data using questionnaires.The results showed that variabe of brand awareness and a significant positive influence on purchasing decisions,perceived quality and significant positive influence on purchasing decisions, brand image and significand positive effect on puchasing decisions and brand loyalty and significant positive effect on purchasing decisions. Keywords: brand awareness, perceived quality, brand image and brand loyalty and purchasing decisions.